The Role of Carbon Risk, Climate Change Exposure and Good Corporate Governance in The Cost of Capital - Nurnaningsih Utiarahman; Fahrudin Zain Olilingo; Raflin Hinelo; Robiyati Podungge (AIBPM Publisher, 2026)
This study examines the influence of carbon risk, climate change exposure, and good corporate governance on the cost of capital in manufacturing companies that go public on the IDX. This study uses a quantitative research approach using secondary data obtained from manufacturing companies that go public on the IDX. The sample consists of 100 observations of manufacturing companies that go public on the IDX, which were selected through purposive sampling. Data analysis was carried out using SPSS